Revising the recent past. Criterio and Esquiú magazines and the human rights issue, 1981-1985 (Quinto Sol, 2015)
In this paper we address the positions taken by two Catholic magazines, Criterio and Esquiú, referring to the review of past and the prosecution of human rights violations between 1981 and 1985. In their interventions is possible to trace political perspectives, interpretations of specific events and different conceptions of the link between religion and politics in the post-dictatorship scenario. In this sense, and bearing in mind that these were Catholic magazines we wonder up to what extent their interventions were permeated by a widespread reconciliatory speech that invoked the hierarchy of the Church and bishops, politicians and military leaders used to claim political decision to close the review of past. We understand that Catholic publications, apart from responding to business logics and cultivating certain links with the readers, are immersed in a power configuration that includes the Catholic hierarchy, and this "hermeneutic pole" should be considered when analyzing their positions.
Keywords: Catholic magazines; democracy; dictatorship; human rights; recent past